(untitled) (Journal of Atomic and Molecular Sciences, 2017)
Organoboron compounds 1-4 with an aryl ring directly bound to a (FMes)2B group through B-C bonds in vacuum, Hexane, Toluene, THF, CH3CN were theoretically studied using DFT with B3LYP functional and 6-31G (d) basis set, and TD-DFT with CAM-B3LYP functional and 6-31G (d) basis set. The absorption and fluorescence spectra of compounds 1-4 are determined in the same and different solvents. It is found that the electronic transition is the most efficient when compounds 1-4 are in CH3CN, the most polar solvent. The spectral contrast of compounds 3 and 4 is studied under different conditions. The charge difference density (CDD) is determined using the data from the intramolecular charge transfer of compounds 1-4 using 3D cube with large oscillator strength.